2018
DOI: 10.1088/1361-6528/aaaaef
|View full text |Cite
|
Sign up to set email alerts
|

Polarized emission from CsPbBr3 nanowire embedded-electrospun PU fibers

Abstract: The interest in all-inorganic halide perovskites has been increasing dramatically due to their high quantum yield, band gap tunability, and ease of fabrication in compositional and geometric diversity. In this study, we synthesized µm long and ~4 nm thick CsPbBr3 nanowires (NWs). They were, then, integrated into electrospun polyurethane (PU) fibers to examine polarization behavior of the composite fiber assembly. Aligned electrospun fibers containing CsPbBr3 nanowires show remarkable increase in degree of pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Apart from their use in PV devices, they show more than 90% quantum yield in photoluminescence; moreover, they possess unique properties, such as solution‐processability, long carrier lifetimes, ease of fabrication, and wavelength tunability . These features make halide perovskites a strong candidate to be used in optical applications, including display technologies, WLEDs, and others . Particularly in the case of WLED applications, these halide perovskites may i) be used together with YAG phosphor; ii) replace YAG phosphor in YAG‐based WLEDs; or iii) be used to obtain three main red‐green‐blue (RGB) colors separately over UV LED, as alternative to UV phosphors.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from their use in PV devices, they show more than 90% quantum yield in photoluminescence; moreover, they possess unique properties, such as solution‐processability, long carrier lifetimes, ease of fabrication, and wavelength tunability . These features make halide perovskites a strong candidate to be used in optical applications, including display technologies, WLEDs, and others . Particularly in the case of WLED applications, these halide perovskites may i) be used together with YAG phosphor; ii) replace YAG phosphor in YAG‐based WLEDs; or iii) be used to obtain three main red‐green‐blue (RGB) colors separately over UV LED, as alternative to UV phosphors.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the reports using perovskite for polarized emission. Although high DOLP ≈0.7 was reported based on an individual perovskite NW,20 the DOLP for a cluster of unordered NWs are still lower than 0.5,21,40 demonstrating the importance of structural alignment for polarization applications. Gao et al have reported an orientationally grown of CsPbBr 3 NW arrays on muscovite mica using chemical vapor deposition (CVD), which possesses the capability to achieve high DOLP of 0.78 41.…”
Section: Resultsmentioning
confidence: 97%
“…However, the anisotropy polarization will be dramatically reduced for NW clusters due to random distribution and disordered arrangement of NWs, which is not practical for the scalable light emission application. As a proof of concept, Güner et al encapsulated CsPbBr 3 NWs into electrospun polyurethane (PU) fibers, but the emitted light from the specimen only showed a DOLP of 0.3 21…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CsPbX 3 quantum dots have great application potential in quantum dot lasers, photodetectors, light-emitting diodes (LEDs), and solar cells. [1][2][3][4][5][6][7][8][9] There have been many routes to prepare this type of semiconductor material, including thermal injection, 10 ligand-assisted supersaturation recrystallization, 11 a microwave-assisted method, 12 and an ion exchange method. 13 Although perovskite quantum dots possess excellent optical properties, their poor stability limits their practical application.…”
Section: Introductionmentioning
confidence: 99%